Osteoclastic cortical erosion as a determinant of subperiosteal osteoblastic bone formation in the femoral neck's response to BMU imbalance. Effects of stance-related loading and hip fracture. - Power, J; Loveridge, N; Lyon, A; Rushton, N; Parker, M; Reeve, J (2005)
Femoral neck fractures have previously been shown to be associated with increased cortical and endocortical remodeling, reduced wall thickness of endocortical packets and cortical porosity. Femoral neck width is associated positively with history of lifetime physical activity; so we hypothesized that exposure to mechanical loading may influence the subperiosteal osteoblastic response to the weakening effect of intracortical bone resorption. In 21 femoral neck biopsies from female subjects (13 with hip fracture), there was a positive association between osteoblastic periosteal alkaline phosphatase expression shown in frozen sections and the percentage of cortical canals internal to the subperiosteal surface showing evidence of osteoclastic erosion (Goldner's stain; p =0.03). This was stronger in the plane of locomotor loading and particularly strong in the inferior (compression) cortex ( p =0.002). In 35 cases and 23 age/gender-matched postmortem controls, osteoid-bearing cortical canals (%) were significantly elevated in the fracture cases compared with the controls within the anterior region. There was also a significant correlation between cortical and endocortical %OS/BS (percentage osteoid surface to bone surface) (fracture, n =12; control, n =12) over the whole biopsy ( p =0.041). Generally, these associations of intracortical with endocortical remodeling were consistent with both envelopes being regulated by common processes. These results support the concept that the slow growth of femoral neck width by subperiosteal apposition of bone occurs directly or, otherwise, in response to the weakening of the cortex as it is "trabecularized" by imbalance of bone multicellular units (BMU). This process, in turn, depends on cortical thinning and enlargement of canals with the formation of giant, composite osteons, the whole being more marked in cases of future hip fracture.